STUDI PENGARUH AERASI DAN RESIRKULASI LINDI TERHADAP LAJU PROSES DEGRADASI SAMPAH PADA BIOREACTOR LANDFILL - Syafrudin, Syafrudin; Pujianto, Bambang; Eko Wahyuni, Sri; Eni Sunarni, Dian; Monalisa, Monalisa (TEKNIK, 2011)
On the conventional landfill, the waste degradation requires a lot of time to make it through and it produces amethane gasfrom a anaerobic which could be dangerous if there is not an optimal processing. On this research,the writer uses 7 experimental reactors, 6 reactors given aeration treatments and leachate recirculation. Thevariations which have done in the research is leachate recirculation debit, namely (10 and 15) ml/minutes andcontinual lacheate’s flowing system and aeration variation, namely (3, 2, and 1)ml/minutes everyday. Theparameter which is measured is the reduction of waste volume, temperature, PH, BOD and COD for weeklyanalysis. The results of the analysis are that the aeration of 1 ml/minutes with leachate resirculation of 15ml/minutes is the best of aeration condition and it can increase the settlement process and reduction of BOD andCOD concentration in a short time of leachate. This reactor can increase the volume reduction as much as 14,14% in six week and it is bigger than control reactor. The concentration reduction of BOD is from 718, 24 mg/lbecomes 88,44 mg/l and the reduction of COD is from 1285,58 mg/l becomes 893,44 mg/l